Entrepreneurial intention among Malaysian undergraduates. - Ismail, Mohammad; Khalid, Shaiful Annuar; Othman, Mahmod; Jusoff, Kamaruzaman; Abdul Rahman, Norshimah; Mohamed Kassim, Kamsol; Shekh Zain, Rozihana (Canadian Center of Science and Education, 2009)
Research in entrepreneurship field has magnetized the interest of many researchers as a tool of development for many countries. The study of the factors that leads people to become entrepreneurs has been a question of many researchers. This study explores the relationship between the Big-Five personality factors, contextual factors and entrepreneurial intention. As such, it fits squarely into the literature on the antecedents of entrepreneurship. Previous research has focused on the need for achievement as well as social psychological characteristics such as attitude and self-efficacy. This study looks at the extraversion, conscientiousness, agreeableness, openness, neuroticism, perceived barriers, perceived support and close support which are determinants of entrepreneurial intention. The data was gathered from 123 undergraduate students at one of the university branch campuses in the northern region of Peninsular Malaysia. Data collection was based on voluntary basis, informed consent, and anonymity. Regression analyses indicate that entrepreneurial intention is positively correlated with extraversion, openness, and close support. In the final section, we discuss these results and discover a future research agenda.